ANALYSIS OF THE EFFECT OF CO2 EMISSION DISCLOSURE, ENVIRONMENTAL PERFORMANCE, CAPITAL INTENSITY, SOCIAL PERFORMANCE, AND COMPANY SIZE ON FINANCIAL PERFORMANCE IN MINING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Rini Oktaria; Erlina; Khaira Amalia Fachrudin (CV. Radja Publika, 2025)
The purpose of this study is to analyze the effect of CO2 emission disclosure, environmental performance, capital intensity, social performance, and company size on the financial performance of mining companies listed on the Indonesia Stock Exchange for the period 2020-2024. This study uses a quantitative approach with secondary data for a period of 5 years. The research population consisted of 63 companies using purposive sampling techniques, resulting in a sample of 17 data points used with panel data regression estimation analysis techniques. The results of this study indicate that CO2 emissions disclosure affects financial performance; environmental performance affects financial performance; capital intensity affects financial performance; environmental performance does not affect financial performance; and company size affects financial performance.